PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE GUIDED NOTE TAKING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 35PADANG TAHUN PELAJARAN 2013/2014 - i Putri, Mai Yun; Delsi K, Delsi K; Harisman, Yulyanti (Pendidikan Matematika, 2014)
ABSTRACTÂ Thebackgroundfrom this research is comprehension studentâsmathematics concept was still low, and the studentâs didnât Â focus on learning the teacher, the results visible of the eighth grade studentâs learn math SMP N 35 Padang. The aim from this research is to know the comprehension studentâs mathematics whice use active learning strategiesGuided Note Taking more better from a comprehension studentâs with use a conventional learning class VIII SMP 35 Padang. A kind from this research is experiment with the random desaign of subject. The instrument used this research isÂ  comprehension studentâs mathematics concept test.The type of test is essay with reliabilitas test is is 0.94. Theanalysis technique data usingon side test twith the help of MINITAB, According to the analysis of data it is know that the two classes are normally distributed and homogeneous samples at Î± = 0.05 and the results obtained from testing the hypothesis P_value = 0.016 is less than Î± = 0.05, so that the hypothesis research is accepted. It can be concluded that the studentâs comprehension of mathematical concepts by applying active learning strategies Guided Note Taking better than the studentâscomprehension of mathematical concepts with conventional learning studentâs in the class VIII SMP N 35 Padang.